2011
DOI: 10.3168/jds.2010-3364
|View full text |Cite
|
Sign up to set email alerts
|

The ensiling capability of a mixture of sodium benzoate, potassium sorbate, and sodium nitrite

Abstract: The objective of this study was to evaluate the effects of an additive comprising sodium benzoate, potassium sorbate, and sodium nitrite on the quality of silages fermented from various forage crops. Thirteen crops in 3 groups (differing in dry matter concentration and degree of ensilability) were treated with the additive mixture and compared with untreated control silages. The main focus was on yeast and Clostridia spp. activity in the silages, although other silage quality criteria also were measured. Treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 14 publications
4
34
1
1
Order By: Relevance
“…Our results indicate that PS and SB may be used alone, rather than in mixtures with sodium nitrite or hexamine, when applied at 1 and 2 g kg −1 to improve silage fermentation. Although Knický and Spörndly () reported that these products might be harmful to the environment and also for human and animal health, Zwiers and Weissbach () stated that the use of neither sodium nitrite nor hexamine presents human or animal health risks.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our results indicate that PS and SB may be used alone, rather than in mixtures with sodium nitrite or hexamine, when applied at 1 and 2 g kg −1 to improve silage fermentation. Although Knický and Spörndly () reported that these products might be harmful to the environment and also for human and animal health, Zwiers and Weissbach () stated that the use of neither sodium nitrite nor hexamine presents human or animal health risks.…”
Section: Discussionsupporting
confidence: 79%
“…The effects of the PS and SB associations or their mixture with other products (EDTA, hexamine, sodium nitrite, sodium propionate) have been explored previously (Lingvall and Lättemäe, ; Knický and Lingvall, ; Kleinschmit et al ., ; Conaghan et al ., ; Knický and Spörndly, ). To be able to test the sole effect of PS and SB, they must be used without any other antimycotic additive.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the low application level, the SALT treatment was capable of improving silage fermentation quality (lower pH on both DM levels, lower acetic acid content on LDM and lower ethanol content on HDM compared to Control treatment) although it is unlikely that the silage additive will prove effective when the Control silage is of relatively good quality, as was the case in this experiment. More positive effects on silage quality parameters with the same SALT treatment were detected by Knicky and Spörndly () especially when the ensiled material was difficult to ensile.…”
Section: Discussionmentioning
confidence: 63%
“…The latest additive mixture, based on a combination of 50 g of sodium nitrite/kg, 200 g of sodium benzoate/kg, and 100 g of potassium benzoate/kg, is reported to have high efficiency for improving silage quality in both high-and low-DM silages (Knicky and Spörndly, 2009). Its efficiency in preventing the growth of undesirable microflora in silages has also been demonstrated for a large variety of crops (Knicky and Spörndly, 2011). However, these results have been obtained in routine ensiling conditions with properly consolidated contents and properly sealed silos.…”
mentioning
confidence: 97%